Epigenetic regulation of synaptic disorder in Alzheimer’s disease - Chen, Zhiying; Wu, Moxin; Lai, Qin; Zhou, Weixin; Wen, Xiaoqing; Yin, Xiaoping (Frontiers in Neuroscience, 2022)
Synapses are critical structures involved in neurotransmission and neuroplasticity. Their activity depends on their complete structure and function, which are the basis of learning, memory, and cognitive function. Alzheimer’s disease (AD) is neuropathologically characterized by synaptic loss, synaptic disorder, and plasticity impairment. AD pathogenesis is characterized by complex interactions between genetic and environmental factors. Changes in various receptors on the postsynaptic membrane, synaptic components, and dendritic spines lead to synaptic disorder. Changes in epigenetic regulation, including DNA methylation, RNA interference, and histone modification, are closely related to AD. These can affect neuronal and synaptic functions by regulating the structure and expression of neuronal genes. Some drugs have ameliorated synaptic and neural dysfunction in AD models via epigenetic regulation. We reviewed the recent progress on pathological changes and epigenetic mechanisms of synaptic dysregulation in AD to provide a new perspective on this disease.